Flux coating enhanced absorption of al surfaces at the characteristic wavelength of co2 laser irradiation - Takacs, Janos; Gal, Peter; Lovas, Antal; Belt, Joachim (Communications - Scientific letters of the University of Zilina, 2000)
Aluminium brazing is a method for joining Al-parts in close proximity by introducing liquid alloys which melt above 577 °C. On the basis of an applied heat source, conventional (flame) and energy-beam brazing (laser) can be distinguished. The laser is capable to result in rapid local melting around the surface to be joined. In spite of the high energy density (represented by laser irradiation) the melting of Al is often unsuccessful. The reason is the low absorption ability of Al at around the wavelength characteristic to the CO2 laser. Coatings with a high absorption ability have to be used in order to facilitate the energy absorption. In the present study the change in absorption ability of Al surfaces due to NOCOLOK© Flux coatings will be presented.